2019
DOI: 10.1016/j.cgh.2018.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Steatohepatitis Is the Fastest Growing Cause of Hepatocellular Carcinoma in Liver Transplant Candidates

Abstract: Nonalcoholic steatohepatitis is the most rapidly growing cause of HCC among US patients listed for liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
468
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 628 publications
(530 citation statements)
references
References 31 publications
10
468
0
8
Order By: Relevance
“…Disease progression in NASH leads to the development of cirrhosis, resulting in various liver‐related outcomes, and is now one of the leading causes for liver transplantation . Other complications such as HCC may develop, with an annual incidence rate of 5.29 per 1,000 person‐years for NASH; and NAFLD is now a frequently observed cause of HCC among liver transplant wait‐listed patients in the United States . Retrospective long‐term follow‐up studies have observed significantly higher unadjusted cumulative probabilities of liver‐related events in patients with NASH …”
mentioning
confidence: 99%
“…Disease progression in NASH leads to the development of cirrhosis, resulting in various liver‐related outcomes, and is now one of the leading causes for liver transplantation . Other complications such as HCC may develop, with an annual incidence rate of 5.29 per 1,000 person‐years for NASH; and NAFLD is now a frequently observed cause of HCC among liver transplant wait‐listed patients in the United States . Retrospective long‐term follow‐up studies have observed significantly higher unadjusted cumulative probabilities of liver‐related events in patients with NASH …”
mentioning
confidence: 99%
“…The United States has had the highest prevalence of severe obesity for several decades . Consequently, it is not surprising that recent data have demonstrated that NASH is becoming an increasingly common indication for liver transplantation (LT) overall and is already the second most common indication for LT in patients with HCC in the United States . In contrast, the demand for LT for hepatitis C virus (HCV) has declined since 2015 following the introduction of safe and effective direct‐acting antivirals.…”
mentioning
confidence: 99%
“…In addition to death and HCC, placement on the waitlist for liver transplantation is an important outcome. NASH has become the fastest‐growing and the second or third leading indication for liver transplantation in the United States …”
Section: Clinical Burden Of Nafldmentioning
confidence: 99%